Bioenergetic myths of energy transduction in eukaryotic cells - Brown, Guy C. (Frontiers in Molecular Biosciences, 2024)
The study of energy transduction in eukaryotic cells has been divided between Bioenergetics and Physiology, reflecting and contributing to a variety of Bioenergetic myths considered here: 1) ATP production = energy production, 2) energy transduction is confined to mitochondria (plus glycolysis and chloroplasts), 3) mitochondria only produce heat when required, 4) glycolysis is inefficient compared to mitochondria, and 5) mitochondria are the main source of reactive oxygen species (ROS) in cells. These myths constitute a 'mitocentric' view of the cell that is wrong or unbalanced. In reality, mitochondria are the main site of energy dissipation and heat production in cells, and this is an essential function of mitochondria in mammals.Energy transduction and ROS production occur throughout the cell, particularly the cytosol and plasma membrane, and all cell membranes act as two-dimensional energy conduits.Glycolysis is efficient, and produces less heat per ATP than mitochondria, which might explain its increased use in muscle and cancer cells.